Character Education Values in the Book of Noble Character Formation by Haidar Putra Daulay and Nurussakinah Daulay - Mohammad Al Farabi; Yusnaili Budianti; Irfan Fiddin (Dinasti International Journal of Education Management And Social Science, 2024)
This research aims to; 1) To analyze the main points of discussion contained in the Values ??of Character Education in the Book Forming Noble Morals by Haidar Putra Daulay and Nurussakinah Daulay, 2). To analyze the Values ??of Character Education contained in the Book Forming Noble Morals by Haidar Putra Daulay and Nurussakinah Daulay, 3). To analyze the contribution of character education in the books Haidar Putra Daulay and Nurussakinah Daulay in forming the character of students in the contemporary era This research uses a qualitative method with a literature study approach. The data sources used are primary data and secondary data. Data collection in this research was carried out by reading and collecting relevant information from identified sources. As well as recording information that is important and relevant to the research topic. The research results show that the books by Haidar Putra Daulay and Nurussakinah Daulay provide a deep understanding of the formation of character values. This can help students recognize Islamic-based character values ??and akhlakul karimah principles that have developed over the centuries. Inspiration from Islamic and Western education figures regarding Positive Psychology. The book encourages students and readers in general regarding their contribution to the formation of the character of Islamic education. Islamic Education Institutions in Indonesia, especially Haidar Putra Daulay and Nurussakinah Daulay, who have also played a role in the renewal and development of Islamic education, can be a source of inspiration. for students to emulate the positive values ??and fighting spirit of these figures.